2018
DOI: 10.1111/jog.13719
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian reserve after internal iliac artery ligation

Abstract: IIAL and hysterectomy are lifesaving interventions during peripartum hemorrhage; however, they might alter ovarian reserve in the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The effects of UAO concomitant with myomectomy (UAO + M) on fertility are unclear . A previous study evaluated ovarian reserve after UAO + M using hormone markers and found no significant effect on subsequent ovarian function, while another study reported short‐term alterations in ovarian reserve in patients undergoing internal iliac artery ligation (IIAL) for post‐partum hemorrhage as assessed based on serum sex hormone levels and ultrasound parameters . To the best of our knowledge, few studies have evaluated the impact of UAO + M to the ovarian reserve, simultaneously using serology, ultrasound parameters and Doppler indices.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of UAO concomitant with myomectomy (UAO + M) on fertility are unclear . A previous study evaluated ovarian reserve after UAO + M using hormone markers and found no significant effect on subsequent ovarian function, while another study reported short‐term alterations in ovarian reserve in patients undergoing internal iliac artery ligation (IIAL) for post‐partum hemorrhage as assessed based on serum sex hormone levels and ultrasound parameters . To the best of our knowledge, few studies have evaluated the impact of UAO + M to the ovarian reserve, simultaneously using serology, ultrasound parameters and Doppler indices.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that IIAL and concurrent hysterectomy can be life-saving interventions in peripartum hemorrhage scenarios. However, these procedures can temporarily reduce serum anti-Müllerian hormone (AMH) levels and ovarian volume in the short term, adversely affecting ovarian reserve [ 22 ]. Our study’s findings prove that no serious complications, such as necrosis in vital organs like the gluteal muscles, legs, bladder, ovaries, and uterus, were seen following the BIIAL procedure due to the interruption of blood flow.…”
Section: Discussionmentioning
confidence: 99%